DAMPAK INVESTASI TIONGKOK DI AFGANISTAN MELALUI PROYEK BELT ROAD INITIATIVE (BRI) - Raihan Ibrahim; Ahmad Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research focuses on the cooperation carried out by Afghanistan-China through the BRI (Belt Road Initiative) in advancing the economy in Afghanistan. This collaboration refers to BRI's policy in which Afghanistan is one of the project countries for land routes through rail facilities as well as connecting ports to ports in countries such as Pakistan and Iran. Several agreements were made between the two countries in the procurement of infrastructure in Afghanistan to make the BRI project a success.This study aims to determine the impact and steps of China in realizing the BRI project. Then this study uses the theory of international cooperation, and the perspective of neo-liberalism as the research basis, as well as the level of analysis of the nation state. By using explanative research methods, and collecting data through library research techniques where the data comes from official documents, a number of journals, and research related news.The results of this study show how China-Afghanistan cooperation in the BRI project has a positive impact on the development of transportation infrastructure in Afghanistan. However, because the project is still ongoing, it is necessary to re-examine it in further research regarding the completion of the BRI infrastructure project in Afghanistan. This is needed to be a reference material for research and studies in the future. Keywords: Belt Road Initiative, cooperation, economy, infrastructure.